Effects of soaking process on arsenic and other mineral elements in brown rice - Fan Zhang; Fengying Gu; Huili Yan; Zhenyan He; Bolun Wang; Hao Liu; Tingting Yang; Feng Wang (Food Science and Human Wellness)
One of the main food crops in the world, rice can accumulate high levels of arsenic from flooded paddy soils, which seriously threatens human health. Soaking, a common processing method for brown rice products, especially for brown rice noodles, was investigated in this study. Japonica rice (Dao Hua Xiang No. 2) and Indica rice (Ye Xiang You No. 3) were selected for studying the effects of soaking on arsenic concentrations, species, and distributions. Results revealed that soaking can efficiently remove arsenic in these two rice varieties, and the main part of removal is endosperm with the maximal rate of about 40%. Inorganic arsenic (I-As) (about 85%) is the main species of arsenic reduction. Meanwhile, the variations of four other elements (i.e., Mg, Ca, Zn, and Fe) were analyzed. Collectively, the findings of this study indicate that soaking can efficiently remove arsenic in brown rice under controlled soaking conditions, which thereby reduces the arsenic intake for brown rice customers.